1978
DOI: 10.1073/pnas.75.4.1859
|View full text |Cite
|
Sign up to set email alerts
|

Physical, morphological, and biochemical alterations in the membrane of AKR mouse cells after interferon treatment.

Abstract: Interferon treatment of AKR,C-cells was followed by the establishment of an antiviral state and apparently concomitant morphological, physical, and biochemical alterations of the cell plasma membrane. The density of the plasma membrane was significantly altered, and the concentration of some plasma membrane glycoproteins and the number of intramembranous particles observed in freeze-fracture electron micrographs were increased. A parallel increase in the concentration of intramembranous particles and the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…IFN (and especially IFN-'y) thus have been reported to modulate the expression of surface antigens. IFN treatment has also been shown to alter cell surface properties, for example, charge (38), mobility of ligand receptors (39), binding of lectins (40), architecture (41), and exposure ofgangliosides (42 …”
Section: Discussionmentioning
confidence: 99%
“…IFN (and especially IFN-'y) thus have been reported to modulate the expression of surface antigens. IFN treatment has also been shown to alter cell surface properties, for example, charge (38), mobility of ligand receptors (39), binding of lectins (40), architecture (41), and exposure ofgangliosides (42 …”
Section: Discussionmentioning
confidence: 99%
“…Inhibition was maximum at 24 h after treatment with 1,000 U of interferon per ml and was dose dependent and reversible with time. Pinocytosis was inhibited when human and chicken embryo cells were treated with homologous, but not heterologous, interferons.In addition to inhibiting viral replication, interferon treatment of cells produces a variety of effects on the plasma membrane (2,3,7,9,12,15) 91:238a, 1981) reported that interferon treatment of thioglycollate-elicited mouse peritoneal macrophages caused a marked change in the distribution of microtubules and 10-nm filaments in a major fraction of the cells; this alteration was correlated with an inhibition of pinocytosis. The results reported here describe some details of the inhibition of pinocytosis in cells treated with interferon.…”
mentioning
confidence: 99%
“…BFA also blocks transport from the ER, and from the trans-Golgi complex to the plasma membrane E4, 7,15]. The proteins within and beyond the trans-Golgi network (TGN) do not return to the ER in the presence of BFA and the transport from post trans-GC compartment to the plasma membrane is not inhibited by BFA [1][2][3]13]. In the present study we have used BFA to further characterize the effect of IFN on intracellular transport of VSV-G and to determine more precisely the site at which transport of G protein to the cell surface in IFN pretreated cell is blocked.…”
mentioning
confidence: 96%
“…The inhibitory effect of IFNs on some enveloped viruses appears to be quite unique, inducing also the release of virus particles with low infectivity and deficient in glycoproteins. Reduced amounts of glycoproteins on released viruses have been described for murine leukemia viruses (MLV), vesicular stomatitis virus (VSV), herpes simplex virus-1 (HSV-1) and bovine parainfluenza-3 virus (PI-3V) [1,2,5,6,12].Mouse LB cells pretreated with IFN (30U/ml) release 10-fold less VSV particles than untreated controls; however, under the same conditions there was observed as much as a 200-fold decrease of viral infectivity [9]. These results suggested that in the presence of IFN not only the production of VSV particles is inhibited, but also the production of noninfectious viruses is enhanced.…”
mentioning
confidence: 99%